If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 14 + -3x = -8x + -25 + x Reorder the terms: 14 + 8x + -3x = -8x + -25 + x Combine like terms: 8x + -3x = 5x 14 + 5x = -8x + -25 + x Reorder the terms: 14 + 5x = -25 + -8x + x Combine like terms: -8x + x = -7x 14 + 5x = -25 + -7x Solving 14 + 5x = -25 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 14 + 5x + 7x = -25 + -7x + 7x Combine like terms: 5x + 7x = 12x 14 + 12x = -25 + -7x + 7x Combine like terms: -7x + 7x = 0 14 + 12x = -25 + 0 14 + 12x = -25 Add '-14' to each side of the equation. 14 + -14 + 12x = -25 + -14 Combine like terms: 14 + -14 = 0 0 + 12x = -25 + -14 12x = -25 + -14 Combine like terms: -25 + -14 = -39 12x = -39 Divide each side by '12'. x = -3.25 Simplifying x = -3.25
| x^3-5x=59 | | C^2-22c+21= | | 4[5y-(y-1)]=7(y-2) | | 21x^2+44x+15=0 | | 62=12 | | 9x=65+4 | | 8(12w+1)= | | 16x^2+4x=12 | | 54-7x=11x+22 | | 108=2(16)+2(L) | | 5(y-3)=5 | | x-8/5=2/4 | | 16x(x-2)-(x-16)=29 | | 22+6m+2m=-15+12m | | 12-9x=45-16 | | 11k-[4k+(-2+6k)]= | | 6(6)+3x=18 | | 6x+3(0)=18 | | 6(0)+3x=18 | | 3p+4=24 | | 12x+7=40 | | 108=2(6+2x)+2(x) | | -12x-1,2=3 | | 20-Gy=18 | | 7-9x=41-16x | | 108=2(6+2w)+2(x) | | 9*(7-4)2+9= | | 230-6x=39x+15 | | 159-2x=25x+15 | | 2-3=11 | | 3(3x-2)+17=7x+3 | | -31x-2x=5-8x |